Scalar politics in Philippine urban disaster management: reframing metropolitan governance for local resilience and sustainability - Gera, Weena (ERDKUNDE, 2018)
Globally, cities are fast becoming the locus of initiatives for building urban resilience and local sustainability. However, imperatives for integration in disaster risk management amid boundary-transcending disasters in urban agglomerations and metropolitan regions, spur new contentions with regards to what constitutes as a responsive construction of the geographic scale and functional scope of the local, particularly in decentralized regimes. This paper assesses the relevance of the Philippines’ current framing of the local jurisdictions, as well as prevailing metropolitan governance arrangements and reform agenda, whether these are responsive to managing disaster variability and their required scales for integrated interventions. Specifically examining the case of urban flooding and management in the country’s major metropolitan regions - Metro Manila, Metro Cebu and Metro Davao – the study identifies the pitfalls of current frameworks of metropolitan disaster governance across the three conurbations, using the lens of scalar politics. It takes off from the different flood risk analyses and integrated flood management master plans proposed for these metropolises, which illustrate the growing salience of the metropolitan region as a crucial scale for positioning urban governance capacity. The paper argues that the Philippines’ construction of local political boundaries does not respond to the needed integration and scale for urban disaster management in metropolitan regions, which remain hijacked in the contestations for political control between and among central and local structures of power. The country’s decentralization system embeds metropolitan governance within the regional administrative governance coordinated by the central government. This creates an ironic capitulation of integrated urban disaster management mandates to central agencies; however, absent political authority, central government-led metropolitan institutions are constrained by prevailing socio-spatial fragmentation. Integrated flood management reforms therefore rely on ad hoc inter-local collaborations that are vulnerable to impasse in inter-jurisdictional negotiations. The study suggests that the Philippines is in a critical juncture to seriously consider reconfiguring its intergovernmental/decentralization system, and adopt a more appropriate scale reference towards institutionalizing political mandates for metropolitan structures. It concludes that responsive reframing of local and metropolitan regulatory authorities, in accordance with required scales and functional scopes of integrated disaster interventions, is a key reform agenda for governments to consider, if they are to seriously promote local capacity for urban resilience and sustainability.